Trends of cancer incidence in Qassim Region, a descriptive analysis of data from the Saudi Cancer registry 2002-2016 - Alshamsan, Bader Ibrahim (International Journal of Health Sciences, 2022)
Objectives: To describe cancer incidence in the Qassim region and compare it with the national incidence rate for all reported cancer sites over 15-years (2002–2016). Methods: A descriptive analysis was conducted using the Saudi Cancer Registry (SCR) data. The annual percentage change (APC) was computed using Joinpoint regression software. Results: The Qassim region contributed to 4.3% (n=6,118) of the total cancer burden in Saudi Arabia (SA). Cancer incidence increased throughout the study period; however, it did not reach statistical significance. The age-standardized rate (ASR) per 100,000 persons was higher in females 68.8 (95% CI: 60.2–77.3) than in males 57.0 (95% CI: 51.9–62.12), p <0.001. Since 2011, colon and rectal cancers have replaced non-Hodgkin lymphoma and liver cancer as the leading cancer types among men. In women, the breast is the leading cancer type, and since 2014, the colon and uterus replaced the thyroid and non-Hodgkin lymphoma as the second and fourth-most common cancers. ASR of nasopharyngeal, esophageal, and Hodgkin's lymphoma were significantly higher in Qassim as compared to SA. The following cancer types showed significant APC (2002–2016): in males; colon: APC = 7.3%, rectum: APC = 6.1%, bone: APC = 8.3%, and esophageal: APC -5.1%. In females; breast: APC = 6%, colon: APC = 7.2%, uterus: APC = 10.1%, kidney: APC = 15.3%, bone: APC = 8.1%, skin non-melanoma: APC = -8.1%, and myeloid leukemia: APC -14.2%. Conclusion: The significant changes in cancer incidence in Qassim warrant further studies on the risk factors and preventive measures.